Health Risk Analysis Due To PM10 and PM2.5 Exposure in Ambient Air in Bandung Regency - Sunardi, Cecep (Jurnal Internasional Penelitian Teknologi Terapan, 2024)
This study aims to identify and analyze non-carcinogenic health risks posed by Particulate Matter (PM10 and PM2.5) exposure in Bandung Regency. The region is experiencing increased emissions of air pollutants due to rapid economic and population growth, especially in industrial and traffic-intensive areas. The study was conducted using the Environmental Health Risk Analysis (EHRA) technique to estimate the public health risks due to PM10 and PM2.5 exposure. Data were obtained through interviews, questionnaires, and direct measurements for PM10 and PM2.5 concentrations. The results showed that the average concentrations of PM10 and PM2.5 in the industrial area of Soreang-Kopo highway were higher (61 μg/m³ for PM10 and 46 μg/m³ for PM2.5) compared to the non-industrial area of Soreang-Ciwidey highway (30 μg/m³ for PM10 and 20 μg/m³ for PM2.5), but still below the quality standards set by regulation, PP RI No. 22 of 2021 which are 55 μg/m³ for PM2.5 and 75 μg/m³ for PM10. The highest level of health risk or RQ for PM10 and PM2.5 is 0.50 so it is declared safe (RQ<1), but even so there are 4 respondents who show RQ values>1, so further risk management is needed such as reducing pollutant concentrations, exposure time, and exposure frequency.